Role of mitochondrial dysfunction in hyperglycaemia-induced coronary microvascular dysfunction: Protective role of resveratrol. (May 2015) - Joshi, Mandar S; Williams, David; Horlock, Duncan; Samarasinghe, Thilini; Andrews, Karen L; Jefferis, Ann-Maree; Berger, Philip J; Chin-Dusting, Jaye P; Kaye, David M
Microvascular complications are now recognized to play a major role in diabetic complications, and understanding the mechanisms is critical. Endothelial dysfunction occurs early in the course of the development of complications; the precise mechanisms remain poorly understood. Mitochondrial dysfunction may occur in a diabetic rat heart and may act as a source of the oxidative stress. However, the role of endothelial cell-specific mitochondrial dysfunction in diabetic vascular complications is poorly studied. Here, we studied the role of diabetes-induced abnormal endothelial mitochondrial function and the resultant endothelial dysfunction. Understanding the role of endothelial mitochondrial dysfunction in diabetic vasculature is critical in order to develop new therapies. We demonstrate that hyperglycaemia leads to mitochondrial dysfunction in microvascular endothelial cells, and that mitochondrial inhibition induces endothelial dysfunction. Additionally, we show that resveratrol acts as a protective agent; resveratrol-mediated mitochondrial protection may be used to prevent long-term diabetic cardiovascular complications.